(Overlooked) Association between Express Bus Station/Stop Proximity and Multifamily Rents with a Surprise about Transit Mode Synergism and Implications for Transit and Land Use Planning. Issue 11 (November 2021) - Nelson, Arthur C.; Hibberd, Robert
Despite hundreds of studies into the association between real estate value and proximity to fixed-route transit (FRT) systems, none has assessed the association with respect to express bus transit (XBT) stations/stops. Ours is the first to do so. Using a static, cross-section quasi-experimental research design, we evaluate CoStar multifamily (MF) rent per square foot to estimate the difference in rent with respect to proximity to XBT stations/stops. However, we are also interested in knowing whether there are synergistic price effects at the intersection of XBT and other FRT systems such as light rail transit (LRT). In this article, we estimate the MF rent premium with respect to XBT and LRT (XBT+LRT) station/stop proximity separately, rent premiums for combined XBT and LRT stations/stops and for those MF cases that are more than 1.0 mi beyond the nearest LRT station. In all cases, whether separately or combined with LRT stations or away from LRT stations, we find positive associations between MF rent and proximity to XBT stations/stops. However, we also find evidence of negative externalities at or near XBT, LRT, and XBT+LRT stations/stops. Express bus transit and land-use planning implications are offered.